Finding My Virginity : The New Autobiography - Branson, Richard (London Virgina Books, 2017)
"50 years ago, Sir Richard Branson started his first business. In his new autobiography, Finding My Virginity, the Virgin Founder shares his personal, intimate thoughts on five decades as the world's ultimate entrepreneur. In Finding My Virginity, Sir Richard Branson shares the secrets that have seen his family business grow from a student magazine into a global brand, his dreams of private citizens flying to space develop from a childhood fantasy to the brink of reality, and his focus shift from battling bigger rivals to changing business for good. Following on from where bestselling Losing My Virginity left off at the dawn of the new millennium, Finding My Virginity takes the reader on a rollercoaster ride with the enigmatic entrepreneur."--Publisher's description.
Include Color Illustration and Index
Keywords: Great Britain -- Businesspeople -- Space tourism